Analytical model of stress analysis for pipeline lowering-in during construction - Xinfeng Pang; Lei Tong; Zhipeng Song; Xiao Sun; Zengcai Li; Lisong Zhang (PLoS ONE, 2025)
During buried pipelines, two construction modes are used, namely, sinking and lowering pipeline into being-dug trench by self-weight, lifting and lowering pipeline into pre-dug trench by hoist. For pipeline sinking and lowering-in, the analytical model was derived especially considering the soil displacement at the end boundary of being-dug trench. For pipeline lifting and lowering-in, the control condition to calculate the lifting force was firstly given based on the extreme displacement of the pipeline. Then, finite difference on the pipeline deflection at each lifting point was performed to obtain the bending moment of the pipeline, and then the lifting point force was derived. Furthermore, the analytical model was established for lifting and lowering-in. By the finite element model and on-site experiment, the analytical models were validated. Results indicated that: (1) taking the length of arched segment, the length of suspended segment, the maximum stress and the bending moment as comparison variables, the maximum errors were 5.56%, 5.96%, 5.35%, 7.36% between the sinking and lowering-in model and the finite element model, while were 8.79%, 4.27%, 8.68%, 8.72% between the sinking and lowering-in model and the on-site experiment; (2) the maximum errors between the lifting and lowering model and finite element model were 7.63%, 8.59%, 3.74%, 6.44%, 9.51% and 8.13%, considering the lifting force and pipeline stress in the vertical plane, the lifting force and pipeline stress in the horizontal plane, and the combined lifting force and combined stress as comparison parameters, and meanwhile the analytical results showed the overall agreement to numerical model at the trench-touched point and the ground-departed point, with the relative errors of 8.59% and 3.68% (in the vertical plane), 5.73% and 4.39% (in the horizontal plane), 6.85% and 4.12% (combined stress), respectively.